One million years tephra record at IODP sites U1436 and U1437: insights into explosive volcanism from the Japan and Izu arcs - Schindlbeck, Julie Christin; Kutterolf, Steffen; Straub, Susanne M.; Andrews, Graham D. M.; Wang, Kuo-Lung; Mleneck-Vautravers, Maryline J. (The island arc, 2018)
The 1 Myr tephra records of IODP (International Ocean Discovery Program) Holes U1436A and U1437B in the Izu-Bonin fore- and reararc were investigated in order to assess provenance and eruptive volumes, respectively. In total, 304 tephra samples were examined and 260 primary tephra layers were identified. Tephra provenance was determined by means of major and trace element compositions of glass shards and distinguished between Japan and Izu-Bonin arc origin of the tephra layers. A total of 33 marine tephra compositions were correlated to the Japan arc and 227 to the Izu arc. Twenty marine tephra layers were correlated between the two drilling sites. Additionally, we defined eleven correlations of marine tephra deposits to major widespread Japanese eruptions; from the 1.05 Ma Shishimuta-Pink Tephra to the 30 ka Aira-Tn Tephra, both from Kyushu Island. These eruptions provide independent time markers within the sediment record and six correlations were used to date tephra layers from Japan in Hole U1436A to establish an alternative age model for this hole. Furthermore, the minimum distal tephra volumes of all detected events were calculated, which enabled the comparison of the tephra volumes that derived from the Japan and the Izu-Bonin arcs. For some of the major Japanese eruptions these are the first volume estimations that also include distal deposits. All of the Japanese tephras derived from events with eruption magnitude Mv ≥ 5.6 and three of the investigated eruptions reach magnitudes Mv ≥ 7. Volcanic events of the Izu-Bonin arc have mostly eruption magnitudes Mv ≤ 5.